2003
DOI: 10.1128/aem.69.9.5414-5422.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Methylation Independent of the Acetyl-Coenzyme A Pathway in Sulfate-Reducing Bacteria

Abstract: Sulfate-reducing bacteria (SRB) in anoxic waters and sediments are the major producers of methylmercury in aquatic systems. Although a considerable amount of work has addressed the environmental factors that control methylmercury formation and the conditions that control bioavailability of inorganic mercury to SRB, little work has been undertaken analyzing the biochemical mechanism of methylmercury production. The acetyl-coenzyme A (CoA) pathway has been implicated as being key to mercury methylation in one SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 54 publications
6
105
1
Order By: Relevance
“…The methylation process has long been known to occur in sub-oxic environments, like sediments or stagnant basins, where inorganic Hg is converted into MeHg by sulfate-reducing bacteria metabolising organic matter. [95,96] There are other interactions between the organic carbon and Hg cycles that are not as well understood. For example, DOM may provide stabilising ligands to maintain Hg in dissolved form, [97] and C-DOM absorbs UV radiation and thus provides an important control on photo-reduction and other photo-initiated processes in surface water.…”
Section: Microbial Carbon Processing and Mercury In The Arcticmentioning
confidence: 99%
“…The methylation process has long been known to occur in sub-oxic environments, like sediments or stagnant basins, where inorganic Hg is converted into MeHg by sulfate-reducing bacteria metabolising organic matter. [95,96] There are other interactions between the organic carbon and Hg cycles that are not as well understood. For example, DOM may provide stabilising ligands to maintain Hg in dissolved form, [97] and C-DOM absorbs UV radiation and thus provides an important control on photo-reduction and other photo-initiated processes in surface water.…”
Section: Microbial Carbon Processing and Mercury In The Arcticmentioning
confidence: 99%
“…Since the study on SRM pure-culture strains Desulfovibrio deseulfuricans first demonstrating its capacity for Hg methylation (Choi et al 1994), many studies linking Hg methylation to SRM species were conducted in natural habitats (Compeau and Bartha 1985;King et al 2000;Benoit et at. 2001;Ekstrom et al 2003). Recently, it was suggested that only SRM belonging to the Deltaproteobacteria group can methylate Hg (Ranchou-Peyruse et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We recently determined the genome sequence for D. desulfuricans ND132 (3) and described its physiological characteristics (17). Desulfovibrio africanus produces MeHg (14) and has different morphotypes associated with a cell cycle (8)(9)(10)18). Its genome sequence was determined and is summarized here to facilitate future analyses into SRBs, mercury methylation, and cell cycle differentiation and regulation.…”
mentioning
confidence: 99%